STRATEGI KEBERHASILAN USAHA DENGAN PENDEKATAN MOTIVASI USAHA SERTA KEMAMPUANUSAHA PADA INDUSTRI MIKRO, KECIL DAN MENENGAH (IMKM) MAKANAN RINGAN DI KOTA SERANG - Qoditul Asrof Ramadoni; Endang Silaningsih (Fakultas Ekonomi Universitas Djuanda, 2017)
This research aims at identifying the strategic of business succes through business motivation approach and entrepreneurship ability in snack’s small-medium industries (SMIs) in Serang City. There were 50 SMIs sampled. The methods used in this research are survey method. The result showed that business motivation (X1) and entrepreneurship ability (X2) simultaneously influencing the business succes of snack’s small-medium industries (SMIs) in Serang City (Y). Whereas, partially all the indicators give both positive and significant affect the business succes of snack’s small-medium industries (SMIs) in Serang City. All the indicators have a contribution factor in this research. Based on Importance and Performance Analysis (IPA) there are three atributte that must be prioritised, which are is practical knowledge of design, processing, accounting, administration and idea, proud to be independet (capital and management), and profit.Keywords : Business Success, Business Motivation and Entrepreneurship ability.